ADOPTIVE CELL THERAPY: CURRENT ADVANCES - T. V. Shamova; A. O. Sitkovskaya; L. N. Vashchenko; E. E. Kechedzhieva (Южно-Российский онкологический журнал, 2020)
The immune system plays an important role in the development and treatment of many cancer types. This fact determined the emergence of numerous immunotherapeutic approaches, including that of adoptive cell therapy (ACT). In this article, we set out to describe the basic methods of adoptive cell cancer therapy, their application and development prospects. The first part of the article deals with the significance of immunotherapeutic methods for cancer treatment and describes the current state of the problem. The main part of the article provides information on the mechanisms of adoptive T cell (unmodified and genetically modified) transfer, the creation of dendritic cell vaccines and cytokine-induced killers (CIK). In addition, a review of recent achievements in the introduction of the aforementioned methods into the clinical practice is carried out. The conclusion is made that adoptive cell therapy can be considered as one of the most promising methods of cancer immunotherapy, which should be optimized for more effective use in the treatment of cancer.